Gold catalysis: alkyl migration in the addition of alcohols to nitriles - Ibrahim, Nada; Hashmi, A. Stephen K.; Rominger, Frank (Advanced synthesis & catalysis, 2011)
Benzhydroles and nitriles upon gold-catalysed conversion deliver symmetrical ethers and/or N-substituted carboxylic amides. While with most phosphane ligands tested, the dominating product is always the ether, with the trimesitylene ligand the amides are the major products. The reaction conditions are much milder than those reported previously. Mechanistic control experiments with a chiral alcohol prove the intermediacy of carbenium ions, further studies with not readily ionisable alcohols indicate that for the benzhydroles the carbenium ions and gold(I)-hydroxy complexes are intermediates.